Legal Implication of Marriage Prenuptial Agreement - Liman, Padma Dewi; Rifai, Aulia (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 12 No 3 (2023)DO - 10.24843/JMHU.2023.v12.i03.p05, 2023)
The purpose of this research will be to see the effectiveness of the decision of the Constitutional Court Number 69/PUU-XIII/2015 dated 27 October 2016 and whether it can solve the problem of regulating marital property in mixed marriages. Meanwhile, the specific target that is expected is whether the arrangements in this marriage agreement can really protect the interests of Indonesian citizen couples in mixed marriages. On the other hand, this study will try to examine what other agreements can be included in the marriage agreement. The type of research used is normative research which is oriented towards legal materials and documents that are relevant to this research. Normative legal research is legal research conducted by examining literature or secondary sources. The research results show that A marriage contract that is retroactively valid should still provide guarantees for legal certainty, but due to differences in views and opinions of the judges handling the case, this results in a discrete decision. A marriage agreement that does not regulate marital assets can be one of the triggers for disputes between husband and wife which can be used as a reason for divorce, whereas if the contents of the marriage agreement regulate marital assets, it can be used to facilitate the distribution of marital assets in the divorce cases.